2023
DOI: 10.3389/fpubh.2022.1021660
|View full text |Cite
|
Sign up to set email alerts
|

Does community-based health insurance reduce disparities in modern health service utilization among households in Ethiopia? A community-based comparative cross-sectional study

Abstract: BackgroundCommunity-based health insurance (CBHI) is an emerging and promising concept to access affordable and effective healthcare by substantially pooling risks to improve health service utilization (HSU) and equity. While there have been improvements in healthcare coverage in Ethiopia, disparities in healthcare remain a challenge in the healthcare system. Hence, the study aimed to assess the effects of CBHI on the reduction of disparities in modern health service (MHS) utilization among households.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…In the study conducted by Fenny et al (2021), they found the inability of some countries' social health insurance programs to cover all groups of people. In Ethiopia, while there have been improvements in healthcare coverage, disparities across places of residence and level of education in healthcare remain a challenge in the healthcare system (Geta et al, 2022).…”
Section: Programs and Services Of Insurance Companiesmentioning
confidence: 99%
“…In the study conducted by Fenny et al (2021), they found the inability of some countries' social health insurance programs to cover all groups of people. In Ethiopia, while there have been improvements in healthcare coverage, disparities across places of residence and level of education in healthcare remain a challenge in the healthcare system (Geta et al, 2022).…”
Section: Programs and Services Of Insurance Companiesmentioning
confidence: 99%